Pemodelan Multiple Discriminant Analysis Pada Perilaku Impulsive Buying Pengguna Shopee Pada Tanggal Cantik - Naue, Siti Nurmeylisya; Yahya, Lailany; Abdussamad, Siti Nurmardia; Payu, Muhammad Rezky Friesta; Nasib, Salmun K (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Impulsive buying is a consumer behavior that makes purchases without prior planning. Impulsive buying is one of the consumer behavior phenomena that is increasingly widespread, especially on e‑commerce platforms such as Shopee during massive promotions on beautiful dates. Multiple Discriminant Analysis (MDA) is a method that has the advantage of classifying individuals into groups based on several predictor variables. The purpose of this study is to classify consumers into groups or categories based on their tendency to make impulse purchases on beautiful dates by analyzing the factors that influence them. The results of this study indicate that the beautiful date can affect the behavior of impulsive buying. The discriminant function model formed is able to distinguish categories of impulsive buying behavior with a good classification accuracy rate of 86.25% and the model shows that price is the most dominant or influential factor in distinguishing the category of impulsive buying of Shopee users on beautiful dates. This means that MDA Modeling is very helpful in classifying respondents into groups or categories based on the factors that influence them.